Book Review: Language Curriculum Design - Humaera, Isna (Celebes Journal of Language Studies, 2022)
The purpose of book reviews as evaluations or critiques is to inform readers and rate the worth of a work. The Language Curriculum Design book by Nation and Macalister (2009) covers the processes involved in the curriculum design process, elaborates on them, provides justifications, and offers opportunities to practice and apply them. This review is an expansion of fourteen chapters. Chapter 1 offers an overview of Chapters 2 through 8, which outline the primary steps of the curriculum design process. The ninth chapter outlines a variety of methods for covering these steps. Involving students in curriculum design, selecting and updating course materials, innovation theory, retraining teachers, and assisting both teachers and students in utilizing a course are discussed in Chapters 10 through 14. Beginning with chapter 1, which provides an overview of language curriculum design, chapters 2 through 8 cover environmental analysis, need analysis, principles, objectives, content and sequencing, format and presentation, monitoring and assessment, and evaluation. In the meantime, chapter 9 provides an overview of curriculum design, while chapters 10 through 13 detail negotiated Syllabi, adopting and altering an existing course book, and implementing change. Planning an In-service course, with the final chapter covering Teaching and Curriculum design.